EFFICACY AND SAFETY OF LOW-DOSE ORAL MINOXIDIL IN THE TREATMENT OF ANDROGENETIC ALOPECIA – A LITERATURE REVIEW - Filip Kieloch; Agnieszka Fitas; Karol Kanon; Mathias Spitaleri; Wiktor Gąska; Oskar Sienkiel; Julia Głowacka; Wojciech Gąska; Dawid Sewruk; Karolina Dębek-Kalinowska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Androgenetic alopecia (AGA) is a chronic progressive form of hair loss affecting a significant portion of the adult population. Although topical minoxidil has a proven efficacy, it is often associated with low adherence due to adverse effects and the inconvenience of use. Increasing attention is being paid to low-dose oral minoxidil (LDOM), which may represent a therapeutic alternative with a favorable safety profile. Purpose of The Work: The aim of this study was to assess the efficacy and safety of low-dose oral minoxidil (≤5 mg/day) in the treatment of androgenetic alopecia based on current clinical trial data. Material and Methods: A narrative literature review was conducted, including studies published in English between 2019 and 2024, concerning the efficacy and safety in patients with AGA. A total of 9 publications meeting the inclusion criteria were analyzed. Results: The analyzed studies demonstrated that LDOM increases both the number and diameter of hair in patients – in both men and women. The best results were observed at doses of 1-5 mg/day, although even very low doses (0.25 mg/day) yielded measurable effects. Adverse events were generally mild – most commonly hypertrichosis and cardiovascular symptoms (e.g., tachycardia), with incidence increasing with dose. Serious complications were rare and occurred primarily in patients with pre-existing heart disease. Conclusion: Low-dose oral minoxidil is an effective and well-tolerated treatment option for AGA. Further studies are needed to standarize dosing and assess the long-term safety of the therapy.